Genetic improvement and related activities. Improvement of individual characters. Drought tolerance - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
During 1986 emphasis was given to testing promising bean germplasm for yields and the 1st materials bred at CIAT specifically for drought tolerance. Preliminary screening was performed under mild stress in the 1st semester, while exceptionally dry weather permitted evaluation under high levels of stress in the 2nd semester. Phaseolus acutifolius lines L172, L174, and L169 gave the highest yields in Palmira and Quilichao, showing their drought tolerance. Given the importance of local adaptation in determining levels of drought tolerance, increased importance has been given to aiding national programs in research of tolerance mechanisms. Basic patterns of response of leaf water potential, stomatal conductance, and canopy temp. in Brazil were similar to those seen at CIAT stations. Results are included in table form. (CIAT)